Densities of the arundo wasp, Tetramesa romana (Hymenoptera: Eurytomidae) across its native range in Mediterranean Europe and introduced ranges in North America and Africa. Issue 8 (3rd August 2018) - Marshall, M.; Goolsby, J. A.; Vacek, A. T.; Moran, P. J.; Kirk, A. A.; Mendoza, E. Cortes; Cristofaro, M.; Bownes, A.; Mastoras, A.; Kashefi, J.; Chaskopoulou, A.; Smith, L.; et al.
ABSTRACT: Tetramesa romana is a biological control agent of the giant reed, Arundo donax (Poaceae: Arundinoideae), which is an invasive weed in the riparian habitats of the Rio Grande Basin of Texas, the southwestern U.S.A. and northern Mexico. Field evaluations were conducted in the native range of T. romana in Mediterranean Europe and in the introduced ranges of Texas, California, and South Africa to compare densities of the wasp. Population densities and percentage parasitism levels for the 2017 year are compared to meteorological variables (average temperature, precipitation, and heat units). In the introduced ranges of Texas (intentional) and South Africa (adventive) T. romana population densities were 39 and 10-fold higher than in the native range, respectively. Percentage parasitism of T. romana in Texas and in the native range of Thessaloniki, Greece were 2.0% and 34.3%, respectively. Annual heat unit accumulation was 1.3–2.7-fold higher at Texas sites than at other introduced or native sites, and heat units were positively associated with exit hole counts at introduced sites. Annual precipitation was 2-fold higher at Texas and South African sites than in California and the native range sites. Favourable weather conditions and reduced parasitism in Texas along the Rio Grande, as compared to the native range, allows T. romana to reach higher population levels and cause considerable damage to A. donax .